The miR-203a Regulatory Network Affects the Proliferation of Chronic Myeloid Leukemia K562 Cells - He, Jinhua; Han, Zeping; An, Ziyi; Li, Yumin; Xie, Xingyi; Zhou, Jiabin; He, Sihua; Lv, Yubing; He, Mengling; Qu, Hong; Liu, Gexiu; Li, Yuguang (Frontiers in Cell and Developmental Biology, 2021)
To study the molecular mechanism by which miR-203a affects the development of CML,bioinformatics software was used to predict the upstream transcription factors and downstream target genes of miR-203a. A 5′-rapid amplification of cDNA ends assay was performed to detect gene transcription initiation sites. A chromatin immunoprecipitation assay was used to verify the binding of transcription factors and promoter regions. A double luciferase reporter gene vector was constructed to demonstrate the regulatory effect of miR-203a on target genes. Real-time PCR and western blotting were used to detect the relative expression levels of genes and proteins, respectively. The results showed that there was a binding site for the transcription factor EGR1 in the upstream promoter region of miR-203a. WT1, BMI1, and XIAP were identified as target genes regulated by miR-203a. EGR1 and miR-203a were downregulated in human peripheral blood mononuclear cells and the CML K562 cell line, while WT1, BMI1, and XIAP were upregulated. The transcription initiation site of miR-203a was identified in the upstream promoter region (G nucleotide at −339 bp), and the transcription factor EGR1 could bind to the promoter region (at −268 bp) of miR-203a and increase its expression. Over expression of miR-203a inhibited the proliferation of K562 cells. A rescue assay showed that overexpression of WT1, BMI1, and XIAP offset the antitumor effect of miR-203a. conclusion, EGR1 positively regulated the expression of miR-203a, thus relieving the inhibition of miR-203a on the translation of its target genes (WT1, BMI1, and XIAP) and affecting the proliferation of K562 cells.